Factors’ influence of E-WOM on travel intentions of tourists: A study on tourist places located in Bangladesh - Akhi, Mst Tasrin Jahan; Sarker, Dr. Mohammad Amzad Hossain; Fakir, Md Kawshar Jahan (Journal of Sustainable Tourism and Entrepreneurship, 2023)
Purpose: This study aimed to determine the effects of electronic word-of-mouth (e-WOM) on tourists’ travel intentions. Research Methodology:  The researchers collected 302 data points using a five-point Likert-scale questionnaire. For this study, a descriptive research technique or methodology was used based on quantitative data. The sampling method was a non-probabilistic convenience sampling method. The SPSS 26.0 version was used for descriptive statistics analysis, reliability testing, and regression analysis. Results: Four independent variables out of five (positive online reviews, negative online reviews, source credibility, and e-WOM quality) had a favorable impact on travelers' plans to travel. Only one variable (e-WOM quality) had no favorable results. Limitations: The study's use of a non-probability convenience sampling strategy was constrained to a certain limited geographic area. There were also issues related to time and money in this investigation. Contribution: This research will help travel organizations understand and acknowledge e-WOM and its significance, as well as develop strategies to manage its effects. In addition, it will help tourists select their tour destinations. Novelty: This study addresses the impact of e-WOM on tourist decision making and explains the complex factors that affect tourists’ decisions to visit a tourist place.